Boycot of transports to the Spanish rebels (circular) - Schevenels, Walther, b. 1894
010-0022-001 FEDERATION SYNDICALE INTERNATIONALE INTERNATIONAL FEDERATION OF TRADE UNIONS INTERNATIONAL GEWERKSCHAFTSBUND 9, AVENUE D'ORSAY, PARIS-VIIe ADRESSE TELEGRAPHIQUE, TELEGRAPHIC ADDRESS, TELEGRAMMADRESSE: INTERFED, PARIS TELEPHONE: INVALIDES 45-88 Situation Espagne 245 Sch/G. 28th December, 1936. To all Affiliated and Sympathising National Trade Union Centres. To all International Trade Secretariats. Dear Comrades, BOYCOT OF TRANSPORTS TO THE SPANISH REBELS. According to the decisions taken at the Joint Meeting of the two Internationals (IFTU/LSI) on the 4th and 5th December and at the Executive Meeting of the International Federation of Trade Unions held on the 17th and 18th December, and with reference to our circular of the 5th August, 1936, we urge all National Trade Union organisations concerned to do their utmost in boycotting any transport of whatever goods there may be despatched or suspected to be despatched to the Spanish rebels. In some countries the workers have already prevented the transport of war material and food to the Spanish rebels. We hope that the Trade Union organisations of all countries will follow our comrades' example, thus strengthening their action, and take all suitable measures that no transport of this kind escapes their attention and these consignments are stopped without delay. We would suggest, for this purpose, the creation of a small permanent Supervisory Committee which would have to track such transports with the help of all organisations concerned and to give all necessary information to these workers' groups which would have to act in case of occurrence. In order to facilitate the international supervision we shall be glad to have at the earliest convenience all information which would be useful for the international coordination of the efforts of the national organisations. We trust that all our affiliated and sympathising organisations will assist unreservedly, by all means and in all spheres, the Spanish Government and people in its fight for its decisive victory. Yours fraternally, W. Schevenels, General Secretary. 292/946/10/22